1998
DOI: 10.1002/j.2161-0045.1998.tb00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraising Cultural Identity in Career‐Development Assessment and Counseling

Abstract: Career-Development Assessment and Counseling (C-DAC) systematically bridges career theory and practice. Integrating differential, developmental, and phenomenological methods, the C-DAC model uses a comprehensive career assessment battery to help clients explore their roles, developmental stages and tasks, career attitudes and knowledge, values, and interests within their unique life contexts. The authors recommend elaborating the C-DAC model to formally appraise cultural identity in step one of the model and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 38 publications
1
48
0
1
Order By: Relevance
“…The list is long (e.g., Arbona, 1990;Bowman, 1995;Chung, 2003;Flores, Berkel, et al, 2006a;Hartung et al, 1998;Leong, 1985;Juntunen et al, 2001;Martin, 1991;Pope, 1995a;Pope et al, 2004;Prince, 1995;Rivera, Chen, Flores, Blumberg, & Ponterotto, 2007;Young, Marshall, & Valach, 2007). It is important to note, however, that the research cited in this article is based on US sources, and, although these keys may be generally applicable in other countries, this cannot be stated definitively.…”
Section: Contextmentioning
confidence: 93%
See 1 more Smart Citation
“…The list is long (e.g., Arbona, 1990;Bowman, 1995;Chung, 2003;Flores, Berkel, et al, 2006a;Hartung et al, 1998;Leong, 1985;Juntunen et al, 2001;Martin, 1991;Pope, 1995a;Pope et al, 2004;Prince, 1995;Rivera, Chen, Flores, Blumberg, & Ponterotto, 2007;Young, Marshall, & Valach, 2007). It is important to note, however, that the research cited in this article is based on US sources, and, although these keys may be generally applicable in other countries, this cannot be stated definitively.…”
Section: Contextmentioning
confidence: 93%
“…Special procedures are recommended for using formal assessment with individuals from the various cultural communities (e.g., Chung, 2003;Chung & Harmon, 1994;Hartung et al, 1998;Leong & Gim-Chung, 1995;Leong & Gupta, 2007;Pope, 1992). Career counselors need to know what special procedures are required in order to get accurate results or to make accurate interpretations.…”
Section: Key #6: Pay Particular Attention To the Role Of The Familymentioning
confidence: 99%
“…In order to increase counsellor empathy, relatedness towards client and counselling effectiveness; it is important that counsellors undergo a parallel process by being exposed to a similar battery of assessment instruments. This will also help counsellors to become more aware of their cultural career development (Hartung et al, 1998;Leong & Hartung, 2003).…”
Section: Developmental Approachmentioning
confidence: 97%
“…It has been suggested that a sixth dimension known as the cultural identity development stage be incorporated so that the primary focus of the model can be on culture. This would allow counsellors to draw attention to culture specific variables such as acculturation, cultural value orientation, external career barriers such as racism or discrimination and special racial group career development stages and behaviours (Hartung et al, 1998). Hartung et al also suggest emphasising this model along three dimensions at the individual, group and universal level so that the model's cultural validity can be increased.…”
Section: Developmental Approachmentioning
confidence: 98%
See 1 more Smart Citation